Differential Effects of Physical and Social Enriched Environment on Angiogenesis in Male Rats After Cerebral Ischemia/Reperfusion Injury - Zhang, Xin; Liu, Jing-Ying; Liao, Wei-Jing; Chen, Xiu-Ping (Frontiers in Human Neuroscience, 2021)
Different housing conditions, including housing space and the physiological and social environment, may affect rodent behavior. Here, we examined the effects of different housing conditions on post-stroke angiogenesis and functional recovery to clarify the ambiguity about environmental enrichment and its components. Male rats in the model groups underwent right middle cerebral artery occlusion (MCAO) followed by reperfusion. The MCAO rats were divided into four groups: the physical enrichment (PE) group, the social enrichment (SE) group, the combined physical and social enrichment (PSE) group and the ischemic + standard conditioning (IS) group. The rats in the sham surgery (SS) group were housed under standard conditions. In a set of behavioral tests, including the modified Neurological Severity Score (mNSS), rotarod test and adhesive removal test, we demonstrated that the animals in the enriched condition groups exhibited significantly improved neurological functions compared to those in the standard housing group. Smaller infarction volumes were observed in the animals of the PSE group by MRI detection. The enriched conditions increased the microvessel density in the ischemic boundary zone, as revealed by CD31 immunofluorescent staining. The immunochemical and q-PCR results further showed that environmental enrichment increased the expression levels of angiogenic factors after ischemia-reperfusion injury. Our data suggest that all three enrichment conditions promoted enhanced angiogenesis and functional recovery after ischemia-reperfusion injury compared to the standard housing, while only exposure to the combination of both physical and social enrichment yielded optimal benefits.